Kissing sebaceous carcinoma of the eyelids: a rare case report - Rao Venkata Mahipathy, Surya Rao; Chandrasekhar, Senthil Kumar Azhisoor; Durairaj, Alagar Raja; Rajamanohar, Vimal Chander; Sundaramurthy, Narayanamurthy; Ramachandran, Manimaran (International Surgery Journal, 2018)
Sebaceous gland carcinomas are tumours of the skin adnexa which occur around the periocular region of elderly females. It is a rare malignancy usually involving the upper eyelid and has an indolent course. Treatment is surgical excision of the lesion with lid reconstruction. Here authors discuss a case of swellings involving both the eyelids of an elderly female diagnosed as sebaceous gland carcinoma on biopsy for which wide local excision and primary eyelid repair was done. This case has been presented as the lesion masquerades as a benign one but is malignant with multifocal spread.